Effect of estradiol and IGF1 on glycogen synthesis in bovine uterine epithelial cells. Issue 3 (1st August 2022) - Gonzalez, Alexis; Berg, Malia D; Southey, Bruce; Dean, Matthew
Abstract : In brief: Glucose is an important nutrient for the endometrium and embryo during pregnancy. This study shows that estradiol (E2)/IGF1 signaling stimulates glycogen synthesis in the uterine epithelium of cows, which could provide glucose when needed. Abstract: Glycogen storage in the uterine epithelium peaks near estrus and is a potential source of glucose for the endometrium and embryos. However, the hormonal regulation of glycogen synthesis in the uterine epithelium is poorly understood. Our objective was to evaluate the effect of E2 and insulin-like growth factor 1 (IGF1) on glycogenesis in immortalized bovine uterine epithelial (BUTE) cells. Treatment of BUTE cells with E2 (0.1–10 nM) did not increase glycogen levels. However, treatment of BUTE cells with IGF1 (50 or 100 ng/mL) resulted in a >2-fold increase in glycogen. To determine if the uterine stroma produced IGF1 in response to E2, bovine uterine fibroblasts were treated with E2, which increased IGF1 levels. Immunohistochemistry showed higher levels of IGF1 in the stroma on day 1 than on day 11, which coincides with higher glycogen levels in the uterine epithelium. Western blots revealed that IGF1 treatment increased the levels of phospho-AKT, phospho-GSKβ, hexokinase 1, and glycogen synthase in BUTE cells. Metabolomic (GC-MS) analysis showed that IGF1 increased 3-phosphoglycerate and lactate, potentially indicative of increased flux through glycolysis. We also found higher levels of N-acetyl-glucosamine and protein glycosylation after IGF1 treatment, indicating increased hexosamine biosynthetic pathway activity. In conclusion, IGF1 is produced by uterine fibroblasts due to E2, and IGF1 increases glucose metabolism and glycogenesis in uterine epithelial cells. Glycogen stored in the uterine epithelium due to E2/IGF1 signaling at estrus could provide glucose to the endometrium or be secreted into the uterine lumen as a component of histotroph.